PERCEPTION OF ADOLESCENTS POSTPARTUM WOMEN’S ABOUT THE NURSING CARE ON THE DELIVERY PROCESS - Luciano Marques dos Santos (Revista Gestão & Saúde, 2013)
This study emphasizes the importance of good assistance and hosting for the parturients, particularly in adolescence, and to understand the adolescent postpartum women’s perceptions about the assistance of the nursing staff in a parturition room after the labor at a public referral hospital in Feira de Santana, Bahia. This is a qualitative descriptive study made through semi-structered interviews with seven puerperals during the first five hours postpartum in october 2008. The data were analyzed using the content analysis methodology. The results showed that the assistance provided to the puerperals was based on the technicist model and thus, the host and humanized care were neglected by the health professionals. It is necessary a reflection about the humanized care and the attitude currently adopted for a better understanding of the condition and human needs.